UNRAVELING THE DYNAMICS: EXPLORING THE VARIED FACTORS IMPACTING STOCK PRICES OF MINING SECTOR FAMILY BUSINESS COMPANIES LISTED ON IDX FROM 2020 TO 2022 - Cahyadi, Hadi; Ervina, Clarrisa (International Journal of Application on Economics and Business, 2024)
Stock are one of the ways to raise capital for a company. Stock prices are influenced by many factors. This research aims to find out the effect of the solvency ratio, firm size, inflation, gross domestic product on the dependent variable, stock price, through the mediating variable,the profitability ratio. The object of this research is mining sector companies managed by families and registered on the IDX in 2020 - 2022. Samples were taken using a purposive sampling technique where the total sample was 81 from 27 companies. This research use the path model with the SmartPLS 4 application. The results of this research are that the solvency ratio has a significant negative effect on stock price and profitability ratio, firm size has a significant positive effect on stock price and profitability ratio, inflation has an insignificant negative effect on stock price and positive insignificant effect on profitability ratio, gross domestic product has an insignificant negative effect on stock price but has an insignificant positive effect on profitability ratio, profitability ratio has a significant positive effect on stock price, the solvency ratio has a significant negative effect on stock price with mediation profitability ratio, firm size has a significant positive effect on stock price with the mediation of the profitability ratio, inflation and gross domestic product have an insignificant positive effect on stock price with the mediation of the profitability ratio.